1972
DOI: 10.1172/jci107117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic hypotonic volume expansion on the renal regulation of acid-base equilibrium

Abstract: A B S T R A C T Balance studies have been carried out to evaluate the influence of vasopressin-induced volume expansion on acid-base equilibrium in normal dogs and in dogs with steady-state metabolic acidosis induced by the administration of 5-7 mmoles/kg per day of hydrochloric acid.Hypotonic expansion in dogs with metabolic acidosis (mean plasma bicarbonate concentration 14 mEq/liter) produced a marked increase in renal acid excretion that restored plasma bicarbonate concentration to normal (20-21 mEq/liter)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Previous studies from this laboratory have indicated that the renal response to HVE causes a striking increase in plasma bicarbonate concentration in animals with chronic HCI acidosis and prevents the anticipated fall in plasma bicarbonate concentration in normal animals (1). In the present study, these effects on acid-base equilibrium were found to be associated temporally with the rise in aldosterone levels.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Previous studies from this laboratory have indicated that the renal response to HVE causes a striking increase in plasma bicarbonate concentration in animals with chronic HCI acidosis and prevents the anticipated fall in plasma bicarbonate concentration in normal animals (1). In the present study, these effects on acid-base equilibrium were found to be associated temporally with the rise in aldosterone levels.…”
Section: Resultssupporting
confidence: 63%
“…2. Note that the data for intact animals used in this figure include not only observations from the present study but also from a previous study of six intact animals treated identically (1). Fig.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…It is likely, therefore, that the transport effects and signaling pathways induced by hyposmolality in the present study are relevant to the response of the MTAL to physiologic decreases in extracellular osmolality in vivo, irrespective of whether those decreases achieve hyposmotic levels (26,41,50). Stimulation of apical membrane Na + /H + exchange activity and HCO 3 -absorption in the MTAL by a fall in osmolality could contribute to the urine acidifying effects of loop-acting diuretics (51,52) and to the increase in urinary net acid excretion that maintains constant the plasma HCO 3 -concentration during hypotonic volume expansion (53). Our findings have additional implications for regulation of sodium balance if hyposmolality stimulates apical Na + /H + exchange activity in other nephron segments such as the proximal tubule, where NHE3 mediates NaCl absorption as well as NaHCO 3 absorption (17,19).…”
Section: Figurementioning
confidence: 99%